Growth and kinetic studies on tropical aquatic plants in the presence of macro-nutrient (nitrate) accumulation. - Tan, Hui Min. (2009)
High levels of nitrate in reservoirs and waterways make the water unsafe for consumption. In addition, the water can become eutrophic, causing it to become unattractive and threatening the aquatic ecology. Wastewater treatment systems which are currently available could generate undesirable by-products and are not cost efficient. Hence, this study investigates the use of phytoremediation as an alternative system to decrease the level of nitrate in water bodies. The nitrate removal rate and growth rate of water spangle (Salvinia molesta), water hyacinth (Eichhornia crassipes), water canna (Thalia dealbata), canna (Canna spp.), papyrus (Cyperus papyrus), elephant ear (Colocasia esculenta), and hydrilla (Hydrilla verticillata) were evaluated in this study. Plastic tanks containing 10L of adapted Hewitt’s solution with 0.16mM of nitrate were used for the investigation. All the plants investigated, except hydrilla, showed different ability in reducing the nitrate level in water. Elephant ear exhibited the greatest rate of nitrate removal at 5.86μM g-1dry wt day-1 and 0.58μM g-1fresh wt day-1. Water spangle showed the highest growth rate, increasing its fresh and dry mass by an average of 71.0% and 21.9% per day, respectively.